ISOLATION OF CYSTEINE AND METHIONINE - BASIL A. ABBAS (Basrah Journal of Veterinary Research)
Random 'l‘n5 mutagenesis produced 2l cysteine/methionine and 13 methionine au.'otrophic mutants of‘ Sinorliiznbimn me/1'/or/' strain Rmd20l. Linkage of Tn5 to auxotroph indicated that each mutant had a single 'l‘n5 insertion. All auxotroph showed spontaneous reversion to prototrophy and they resembled the parental strain in production ofcell surface molecule and utilization of sugars and dicarboxylic acid.